2015
DOI: 10.1371/journal.pone.0135210
|View full text |Cite
|
Sign up to set email alerts
|

Ground-Dwelling Arthropod Communities of a Sky Island Mountain Range in Southeastern Arizona, USA: Obtaining a Baseline for Assessing the Effects of Climate Change

Abstract: The few studies that have addressed past effects of climate change on species distributions have mostly focused on plants due to the rarity of historical faunal baselines. However, hyperdiverse groups like Arthropoda are vital to monitor in order to understand climate change impacts on biodiversity. This is the first investigation of ground-dwelling arthropod (GDA) assemblages along the full elevation gradient of a mountain range in the Madrean Sky Island Region, establishing a baseline for monitoring future c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…In the latter, a different pattern of the spider diversity shift was detected among the two studied slopes with different precipitation regimes (Foord & Dippenaar‐Schoeman, ). Additionally, Meyer et al () revealed seasonal differences in ground‐dwelling arthropod communities along an elevational gradient in the subtropical southwestern US but did not further dissect their patterns or drivers. All these studied areas are also characterized by intra‐annual cycles of dry and wet seasons similar to our tropical locality.…”
Section: Discussionmentioning
confidence: 98%
“…In the latter, a different pattern of the spider diversity shift was detected among the two studied slopes with different precipitation regimes (Foord & Dippenaar‐Schoeman, ). Additionally, Meyer et al () revealed seasonal differences in ground‐dwelling arthropod communities along an elevational gradient in the subtropical southwestern US but did not further dissect their patterns or drivers. All these studied areas are also characterized by intra‐annual cycles of dry and wet seasons similar to our tropical locality.…”
Section: Discussionmentioning
confidence: 98%
“…Making comparisons of species richness is difficult among and within regions, particularly with ground‐dwelling spiders, because an enormous, resource‐intensive effort is required to obtain a relatively complete inventory (Meyer et al. ). Because of the number of species we collected and the scale of our study, our results suggest that Southern California, particularly Claremont, CA, harbors a fairly diverse spider assemblage.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Meyer et al. () found 102 spider species in six plant biomes along an elevation gradient in the Santa Catalina Mountains in Arizona using a much higher number of pitfall traps (660 over two seasons; 9240 trap days) and sampling an area with six distinct plant biomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pilot data collected in 2010 suggested this design effectively captured the ground-dwelling arthropod community we observed through visual observations at these sites, and similar trapping schemes have been used to investigate ground-dwelling arthropod communities in the region (e.g., McCluney & Sabo, 2012;Meyer et al, 2015). Pilot data collected in 2010 suggested this design effectively captured the ground-dwelling arthropod community we observed through visual observations at these sites, and similar trapping schemes have been used to investigate ground-dwelling arthropod communities in the region (e.g., McCluney & Sabo, 2012;Meyer et al, 2015).…”
Section: Methodsmentioning
confidence: 99%